Sceny wspólnej uwagi w nauce czytania wspomaganej komputerowo - Juszczyk, Konrad (Investigationes Linguisticae, 2007)
This article is to explain how computer programs can teach children to read. The children-computer interaction is analyzed as a joint attentional frame. It is argued that children interact with computer and avatars (life-like characters) in educational programs because they treat them like other people (media equation) and act like in a joint attentional frame. The article consists of four parts. The first part is an introduction showing a broad background of this research. The second part presents current views on language acquisition in cognitive linguistics framework which is a Tomasello?s socio-pragmatic theory. The third part is an analysis of some educational programs in terms of joint attentional frame with emphasis on Colorado Literacy Tutor. The last part suggests that children do treat avatars as people because they perceive them like the self, which is a consequence of being brought up in a series of joint attentional frames.